Enterococcal PcfF Is a Ribbon-Helix-Helix Protein That Recruits the Relaxase PcfG Through Binding and Bending of the oriT Sequence - Rehman, Saima; Li, Yang Grace; Schmitt, Andreas; Lassinantti, Lena; Christie, Peter J.; Berntsson, Ronnie P.-A. (Frontiers in Microbiology, 2019)
The conjugative plasmid pCF10 from Enterococcus faecalis encodes a Type 4 Secretion System required for plasmid transfer. The accessory factor PcfF and relaxase PcfG initiate pCF10 transfer by forming the catalytically active relaxosome at the plasmid’s origin-of-transfer (oriT) sequence. Here, we report the crystal structure of the homo-dimeric PcfF, composed of an N-terminal DNA binding Ribbon Helix Helix (RHH) domain and a C-terminal stalk domain. We identified key residues in the RHH domain that are responsible for binding pCF10’s oriT sequence in vitro, and further showed that PcfF bends the DNA upon oriT binding. By mutational analysis and pull-down experiments, we identified residues in the stalk domain that contribute to interaction with PcfG. PcfF variant proteins defective in oriT or PcfG binding attenuated plasmid transfer in vivo, but also suggested that intrinsic or extrinsic factors might modulate relaxosome assembly. We propose that PcfF initiates relaxosome assembly by binding oriT and inducing DNA bending, which serves to recruit PcfG as well as extrinsic factors necessary for optimal plasmid processing and engagement with the pCF10 transfer machine.